THE INFLUENCE OF ORGANIZATIONAL CULTURE AND JOB SATISFACTION ON OCB WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE - Nuria Fitri Ramadani; Ismartaya; Silaningsih, Endang (Jurnal Visionida, 2025)
This research was conducted to determine the effect of organizational culture and job satisfaction on organizational citizenship behavior through organizational commitment as an intervening variable in employees. This research design uses descriptive and verification methods with a quantitative approach. In determining the research sample, the authors used probability sampling with simple random sampling technique and used the degree of variability sample measurement, obtained as many as 134 employees. The analysis method used is path analysis with t test and sobel test. The results showed that organizational citizenship behavior of employees through organizational culture, job satisfaction and organizational commitment in Pusdiklatwas BPKP employees is in the good category; organizational culture has a direct and positive effect on organizational commitment; job satisfaction has no direct and positive effect on organizational commitment; organizational culture has a direct and positive effect on organizational citizenship behavior; job satisfaction has a direct and positive effect on organizational citizenship behavior; organizational commitment has a direct and positive effect on organizational citizenship behavior; organizational culture has an indirect and positive effect on organizational citizenship behavior through organizational commitment; job satisfaction has no indirect and positive effect on organizational citizenship behavior.